FDG-PET in Hodgkin lymphoma - Kobe, C.; Dietlein, M.; Mauz-Körholz, C.; Engert, A.; Borchmann, P.; Sabri, O.; Schober, O.; Schicha, H.; Kluge, R. (Nuklearmedizin - NuclearMedicine, 2008)
The high negative predictive value of FDG-PET in therapy control of Hodgkin lymphoma is proven by the data acquired up to now. Thus, the analysis of the HD15 trial has shown that consolidation radiotherapy might be omitted in PET negative patients after effective chemotherapy. Further response adapted therapy guided by PET seems to be a promising approach in reducing the toxicity for patients undergoing chemotherapy. The criteria used for the PET interpretation have been standardized by the German study groups for Hodgkin lymphoma patients and will be reevaluated in the current studies.
Keywords: PET; Hodgkin lymphoma; response-adapted design; chemotherapy; radiotherapy